Avaliação da colmatação biológica através da atividade enzimática em filtros lentos intermitentes para uso unifamiliar - Puhl, Vanessa de Andrade (2021)
Water supply in rural communities without access to treatment is a challenge to be overcome. In this perspective, a simple, accessible and easy-to-use technology, such as the domestic biological filter, maybe a viable alternative. The study aimed to evaluate the enzymatic activity by microorganisms involved in the filtration process in intermittent slow filters. The evaluation of microbial indicators in-depth in the filter medium was carried out through enzymatic tests according to the hydrolysis of fluorescein diacetate and the degradation of triphenyltetrazolium chloride, in addition to organic matter. Three columns (triplicate) were filled with Fine sand (d10 = 0.16 mm) with an initial filtration rate of 1.19 x10-4 m/s and another three columns (triplicate) with Medium sand (d10 = 0.45 mm) and initial filtration rate of 5.39 x10-4 m/s. The columns were operated with a downward flow regime and intermittent flow. Daily monitoring of raw water from a lake in a permanent preservation area and filtered water was carried out, according to physical parameters (turbidity, temperature, apparent and true color), chemical (dissolved oxygen, pH and electrical conductivity), and hydraulic (filtration rate and hydraulic conductivity), in a single filtration run (115 days). A statistical test was performed using analysis of variance (ANOVA) to compare means and significance using the Tukey test. Minor variations in water quality were observed during acclimatization phase of the columns. Afterwards, stability was favorable to microbiological development demonstrated with enzymatic tests. The particle size characteristics did not significantly differ between physical and chemical aspects of water quality. It was possible to notice microbiological activity along filters' depth through enzymatic assays and analysis of the organic matter related to biological clogging. Oscillation points of the identified concentrations are probably due to the particle size distribution used, which allowed the percolation of particles and microorganisms to deeper layers, resulting in internal clogging. It was found that the presence of dehydrogenase through TTC maintained oscillating concentrations in-depth. In the FDA's enzymatic hydrolysis assay, it was possible to visualize evidence of greater biological activity in the first layers of the filter media and its decay in-depth. It is concluded that under these hydraulic conditions, the filters can operate for long periods, presenting low clogging and providing a longer useful life to the filter.